(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article presents the results of the experimental studies conducted to study the influence of the opening angle of the soil pusher of the combined machine leveler used in the preparation of land for planting on the performance indicators of the leveler.